Development of an experimental variable temperature set-up for a temperature range from 2.2 K to 325 K for cost-effective temperature sensor calibration. (23rd March 2017) - Pal, Sandip; Kar, Ranjan; Mandal, Anupam; Das, Ananda; Saha, Subrata
Abstract: A prototype of a variable temperature insert has been developed in-house as a cryogenic thermometer calibration facility. It was commissioned in fulfilment of the very stringent requirements of the temperature control of the cryogenic system. The calibration facility is designed for calibrating industrial cryogenic thermometers that include a temperature sensor and the wires heat-intercept in the 2.2 K–325 K temperature range. The isothermal section of the calibration block onto which the thermometers are mounted is weakly linked with the temperature control zone mounted with cooling capillary coil and cryogenic heater. The connecting wires of the thermometer are thermally anchored with the support of the temperature insert. The calibration procedure begins once the temperature of the support is stabilized. Homogeneity of the calibration block's temperature is established both by simulation and by cross-comparison of two calibrated sensors. The absolute uncertainty present in temperature measurement is calculated and found comparable with the measured uncertainty at different temperature points. Measured data is presented in comparison to the standard thermometers at fixed points and it is possible to infer that the absolute accuracy achieved is better than ±0.5% of the reading in comparison to the fixed point temperature. The design and development of simpler, low cost equipment, and approach to analysis of the calibration results are discussed further in this paper, so that it can be easily devised by other researchers.